Prototyping studies for self-sufficient power machines with local resources from the Moon - Ferreiro Garcia, Ramon (JOURNAL OF ADVANCES IN PHYSICS, 2025)
This paper investigates the design challenges of implementing Self-Sustaining Power Machines (SSPMs) for lunar environments using in-situ resources. These machines are engineered to provide on-site energy in the form of heat, mechanical work, or electrical power as required for lunar operations. Given that SSPMs rely on a thermal working fluid for functionality, a key aspect of the design process involves the selection and optimization of this fluid. Lunar regolith contains trapped gases that can be extracted and utilized—an approach known as In-Situ Resource Utilization (ISRU). Among the available candidate gases (helium, argon, and neon), this study evaluates two SSPM designs compatible with these fluids. These innovative prototypes employ cutting-edge technologies to generate mechanical work through pulling forces, achieved via cooling rather than conventional heating. Notably, the system recovers and regenerates waste cooling heat, enabling reuse without external energy input. The proposed design framework incorporates a combined cycle (CC) integrating a reverse Brayton cycle (RBC)-based heat pump with an SSPM composed of cascaded power units (PUs). The CC prototype (RBC + SSPM) was tested using helium, argon, and neon obtained through ISRU. Results (Tables 27 and 28) demonstrate that the SSPM-based CC, configured with six PUs operating in a VsVs cycle, achieves a self-sufficient net work output at viable efficiency levels